Sacred word and sacred text: scripture in world religions - Coward, Harold G. (Orbis Books, 1988)
This attractively produced and cleanly stated book is something of an anomaly: it is a flawed good book. Despite editorial and authorial attempts to adhere to the agenda of summarizing the oral/written dichotomy as it effects sacred words, this volume is, fundamentally, a comparativereligion text. Furthermore, it is more than suitable for lay reading, but far too scholarly for most lay appetites, the result being that the reader is frequently unsure of exactly whom Professor Coward is addressing with his thesis and for what reason. The religions discussed likewise seem to be somewhat idiosyncratic. There is the predictable "big four" of Judaism, Christianity, Hinduism, and Buddhism. They are joined by Sikhism. As the poet says, '~Only this and nothing more." Despite these disconcerting elements, however, Sacred Word and Sacred Text is a clearly argued explication of the potency of the oral word in worship, religious education, and private devotion. Within each tradition discussed, Coward presents the history of the sacred message as it has developed within that tradition as both spoken (word) and written (text) revelation. His parallel approach illuminates grippingly the religious uses of the spoken/written and convinces the believing heart as well. Those who have experienced deep concern about changes in the liturgy and its texts, those to whom the care of young children is entrusted, those who-perceiving themselves to be in a post-modem, post-literate era--are seeking vital ways to convey era-less truths, those who seek efficacy in prayer-for all of these arid, perhaps, for others, Sacred Word and Sacred Text may provide a strong historical and comparative context for the persistent reader